Genetic resources in pomology: Consultant final report IICA/EMBRAPA PROCENSUL II - Hough, Leon Fredic (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The title of activity of IICA Project corresponding to this consultancy is cooperation with EMBRAPA, on research and applications of genetic resources, biotechnology and biologic control of pests diseases and weeds, especially, genetic resources-pomologist.